Qualitative Study Of Knowledge Sharing To Improve Employee Performance Through The Implementation Of Occupational Safety And Health Management System (SMK3) And Zero Accident At Palm Oil Mill In West Kalimantan Province - Zainal Abidin (Journal Of Social Science (JoSS), 2023)
This research is a qualitative study that aims to explore the impact of implementing the Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) and Zero Accident on improving employee performance through the knowledge-sharing process. The research method involved in-depth interviews with factory management, supervisors, and employees, as well as on-site observations. Data analysis was conducted using a qualitative approach, highlighting key findings related to the implementation of Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3), Zero Accident, and knowledge-sharing practices in the work environment. The results showed that the implementation of Zero Accident significantly influenced the awareness of occupational safety and health among employees. The knowledge-sharing process was identified as a key factor in improving collective understanding of safety practices, as well as improving overall performance. The findings contribute to further understanding of how Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) integrity and Zero Accident can be combined with knowledge-sharing practices to achieve a safer and more productive work environment. The implications of this study can provide practical guidance for palm oil mills and similar industries to improve the effectiveness of their safety strategies by considering knowledge sharing as an important component in developing a sustainable safety culture.